Asas Tunggal Pancasila dan Upaya Memaknai Kembali “Stabilisasi” Politik Indonesia - Amsar A. Dulmanan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2015)
This paper deals with the single principle of Pancasila and efforts to redefine the "stabilization" of Indonesian politics. Ideological strengthening measures are based on the historical power of Indonesia, which is filled with a variety of conflicts and conflicts within community groups, in political parties or in elites in state institutions, especially in competition, polarization of political interests and ideological background. The concept of ideology cannot be destroyed, always dynamizing itself as an awareness that is believed by many people, groups or within political party institutions. From this understanding, at least the New Order patterned a political awareness about the necessity of Pancasila to become an ideology of the state in the direction of an ideological awareness in a life together in a community, becoming a nation within the Indonesian state.